An investigation of mHealth and digital health literacy among new parents during COVID-19 - Donelle, Lorie; Hiebert, Brad; Hall, Jodi (Frontiers in Digital Health, 2024)
Especially during the COVID-19 pandemic, parents were expected to understand increasingly sophisticated information about health issues and healthcare systems and access online resources as a part of their caregiving role. Yet little is known about parents’ online digital technology use and digital health literacy skill. This study aimed to investigate parents’ digital technology use, their self-reported digital health literacy skill, and demographic information as potential factors influencing their use of digital technologies. Methods: An online survey utilizing convenience sampling was administered to new parents during the COVID-19 pandemic that inquired about their demographic information, digital technology use, and digital health literacy skills within Ontario, Canada. Results: A total of 151 individuals responded to the survey; these were primarily mothers (80%) who self-reported as white (72%), well-educated 86%), heterosexual (86%) females (85%) with incomes over 100,00 per year (48%). Participants reported consistent and persistent online activity related to their parenting role and mostly via mobile smartphone devices (92%). Participants had moderate to high digital health literacy skills, greater than the Canadian national average. Almost half of participants reported negative health and well-being consequences from their digital online behaviours. There were no significant relationships between technology use, digital health literacy skill, and demographic variables. Discussion: The COVID-19 pandemic has reinforced the need for and importance of effective and equitable digital health services. Important opportunities exist within clinical practice and among parenting groups to proactively address the physical and mental health implications of digital parenting practices. Equally important are opportunities to insert into clinical workflow the inquiry into parents’ online information-seeking behaviours, and to include digital health literacy as part of prenatal/postnatal health education initiatives.